Gratitude learning as an effort to increase self-acceptance for high school students in Ambon City - Wenno, Yulian Hermanus; Rampisela, Theophanny P. Th. (International Journal of Education, Information Technology, and Others, 2023)
In the second year of research (2021), researchers using regular gratitude journal writing have increased the mean pre-test and post-test scores with a total mean post test score of 36.00 which is greater than the mean pre-test score, namely 31.83 of the total score. 42. Then a gratitude learning module was created which could have an impact on other variables, namely the variable of self-acceptance. The researcher took the same population and subjects as in the previous research using a saturated sample technique which took the entire population of students in class XI and to see the linear relationship of the two variables. The results of the hypothesis test show a significant influence between learning to be grateful and students' self-acceptance if seenin class_gratitude 1 (low group), gratitude learning did not significantly influence performance (p<0.05) with Sig. = 0.084. Meanwhile, in class_Gratitude 2 (high group), learning to be grateful has a significant effect on performance (p<0.05) with a Sig. = 0.018. From the results it can be seen that there is actually an influence between Appreciative Learning and Student Self-Acceptance.